Estimation of fatty components and study the composition of fatty acids in serum for fatty liver disease patients - Mohammed Jasim (College of Education for Pure Sciences, 2009)
ِAbstract The study was designed to estimate the effect of fatty liver disease on the level of some biochemical parameters, percentage of fatty acids in serum lipids. the study includes (25) fatty liver patients as verified by ultrasonography of the liver, the age ranged between (50-70) year and (25) apparently healthy subjects of matched age group. The some biochemical parameters were measured as well as analysis and measurement of Percentage and level of fatty acids in serum lipids, lipids extraction from serum and separation of serum lipids (Cholesterol ester, Triglyceride, Phospholipids) by TLC, and then esterification of fatty acids and measurement of percentage of fatty acids by Capillary Gas Chromatography (CGC). the result showed that there was large effect of fatty liver disease on the biochemical parameters and the percentage of fatty acids comparison with control group